Macchina creativa e genesi temporale nella metafisica di A.N. Whitehead (Nóema, 2015)
This article is about Whitehead's metaphysics. We focus on operations constituting the processual character of this philosophy. The approached problems are the organization of genetic space of concrescence and co-ordinate space of transition, the complex dynamics between nature and abstraction then the reciprocity between a subjective and affective formation and a neutral temporality of duration's blocks. The intuition behind our reflection is that there is a principal concept which animates  Whitehead's cosmology of Creativity : the concept of Becoming.
Keywords: Whitehead; process; nature; abstraction; duration; becoming